Paediatric nurses’ attitudes towards the promotion of healthy eating in children and their families. - Patterson, Joanna Charlotte (2013)
Background Obesity is a significant public health issue causing many ill-effects. Arguably nurses should be advocates and role models for healthy eating promotion as part of obesity prevention. However, there is limited research available relating specifically to paediatric nurses as health promoters, their promotion of healthy eating or their attitudes towards being role models for health behaviours. Objectives To investigate paediatric nurses’ attitudes towards the promotion of healthy eating in children and their families. To investigate whether personal health factors (in this case body weight) of paediatric nurses has any influence on their attitudes towards the promotion of healthy eating in children and their families. Method A cross-sectional questionnaire survey was conducted across the paediatric wards and departments at Nottingham University Hospitals NHS Trust. The questionnaire assessed participants’ attitudes towards paediatric nurses being role models for health promotion and towards the promotion of healthy eating to children and families, including their self-efficacy as a factor within this. Findings The main findings of this study were that participants’ attitudes towards healthy eating promotion and paediatric nurses as role models were not always consistent with their actions. Self-efficacy and a disagreement regarding whose responsibility health promotion was were further factors affecting participants’ attitudes. Although many participants felt that they could improve their health promotional practices, their knowledge of healthy eating, and their own health behaviours need to be significantly improved first. Conclusions A qualitative study would allow for further exploration of paediatric nurses’ attitudes towards the promotion of healthy eating in children and their families. Furthermore, with more time and resources, a study could be carried out in multiple centres so as to gain a wider understanding of attitudes, as well as producing results that can be better generalised to paediatric nurses as a whole population.